Solar-Assisted IoT-Based Smart Home for Energy Efficiency and Hazard Prevention Toward Sustainable Living - Fitriyan, Rahmawati; Syafii, Syafii (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This study presents the development of a solar-assisted smart home system based on the Internet of Things (IoT) that focuses on energy efficiency and hazard prevention as a contribution to sustainable living. The proposed system integrates renewable energy utilization with intelligent monitoring to reduce energy consumption and minimize carbon footprint. A Raspberry Pi microcontroller is employed as the central platform to coordinate multiple sensors, including a DHT11 sensor for temperature and humidity measurement, a gas sensor for leak detection, a vibration sensor for earthquake monitoring, and a PZEM-004T module for real-time energy consumption tracking. The system enables remote supervision and automated responses to environmental hazards while maintaining comfort and security for occupants. Experimental results demonstrate that the prototype enhances early warning capability for potential fire incidents and natural disasters, while significantly improving energy awareness through continuous monitoring. The integration of solar energy further supports the sustainability aspect, making the system a viable smart solution for greener and safer residential environments.